2012
DOI: 10.1177/1076029612438611
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of Using Thrombin Generation Assay (TGA) for Monitoring Bypassing Agent Therapy in Patients With Hemophilia Having Inhibitors

Abstract: In conclusion, we found that the clinical effectiveness of bypass therapy in hemophilia cannot be assessed by TGA and TEG.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
23
2
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 35 publications
0
23
2
1
Order By: Relevance
“…56 The expert suggests that therapy of bleeding episodes in patients with FVIII inhibitor by rFVIIa has faster response compared to aPCC. [55][56][57][58][59] In this study, baseline characteristics of patients were comparable to other studies considering the age, bleeding severity and FVII levels before and after intervention, and FVIII inhibitor plasma level. 9,14,56 The number of patients with hemophilia having inhibitor who were treated in most reported trials varied from 15 to 62; in the current study, the sample size was 66 patients.…”
Section: Discussionmentioning
confidence: 53%
See 3 more Smart Citations
“…56 The expert suggests that therapy of bleeding episodes in patients with FVIII inhibitor by rFVIIa has faster response compared to aPCC. [55][56][57][58][59] In this study, baseline characteristics of patients were comparable to other studies considering the age, bleeding severity and FVII levels before and after intervention, and FVIII inhibitor plasma level. 9,14,56 The number of patients with hemophilia having inhibitor who were treated in most reported trials varied from 15 to 62; in the current study, the sample size was 66 patients.…”
Section: Discussionmentioning
confidence: 53%
“…We checked mean levels of FVII before and after administration of the 2 rFVIIa preparations to prove FVII: C level was comparably increased. 6,38 In the previous studies, the rate of reported adverse events was 1% to 10%, [50][51][52][53][54][55][56][57][58][59][60] and the most of adverse events had been headache, rashes, hypertension, and rarely thrombosis. We did not encounter any thrombosis in either treatment groups.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Отношение к использованию этих интегральных тестов для мониторинга действия rFVIIa в литературе неоднозначное. При обследова-нии 7 больных с ингибиторной формой гемофилии, получавших шунтирующие препараты (rFVIIa, акти-вированный протромбиновый комплекс), не выявле-но связи между клиническим ответом на их введение и изменениями, регистрируемыми с помощью ТЭГ или теста генерации тромбина [12]. В то же время в многоцентровом исследовании введение rFVIIa в дозе 90 мкг/кг, т. е. в той же дозе, что и в нашем ис-следовании, проводило к нормализации параметров ТЭГ у больных с ингибиторной формой гемофилии [13].…”
Section: Discussionunclassified